Linda Carlson preparing drawers - Unidentified photographer (Colorado State University. Libraries, 2008)
Photograph of Curator Linda Carlson preparing drawers for the collection move out of the Gifford Building in 2008.
Keywords: Fashion -- History; Fashion -- Exhibitions